Effects of different forms of chitosan on intercellular junctions of mouse fibroblasts in vitro - ÖZBAŞ, SUNA (TAYLOR & FRANCIS INC, 2016)
Chitosan is a linear polysaccharide that has many biomedical applications. We compared the effects of chitosan, in both solution and membranous form, on intercellular adhesion of Swiss 3T3 mouse fibroblasts. Cells were grown as spheroidal cell cultures. Some control cell spheroids were cultured without chitosan and two experimental groups were cultured with chitosan. Chitosan in solution was used for one experimental group and chitosan in membranous form was used for the other. For each group, intercellular adhesion was investigated on days 5 and 10 of culture. Transmission electron microscopy revealed well-defined cellular projections that were more prominent in cells exposed to either membranous or solution forms of chitosan than to the chitosan-free control. Immunocytochemical staining of ICAM-1 and e-cadherin was used to determine the development of intercellular junctions. Compared to the weakly stained control, strong reactions were observed in both chitosan exposed groups at both 5 and 10 days. Cells were treated with 5-bromo-2-deoxyuridine (BrdU) and incubated with anti-BrdU primary antibody to assess proliferation. Both the solution and membranous forms of chitosan increased proliferation at both 5 and 10 days. Cellular viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT). The MTT assay indicated high cell viability; maximum viability was obtained with the solution form of chitosan at day 5. Chitosan exposure increased the number of intercellular junctions and showed a significant proliferative effect on 3T3 mouse fibroblasts.
Keywords: chitosan; e-cadherin; electron microscopy; ICAM-1; TISSUE ENGINEERING APPLICATIONS; GENE DELIVERY; CHITIN; HYDROGEL; PROLIFERATION; SCAFFOLDS; ADHESION; GROWTH; DEGRADATION; MACROPHAGES